True Legend - Lupica, Mike (New York : Philomel Books, 2012)
Fifteen-year-old Drew "True" Robinson loves being the best point-guard prospect in high school basketball, but learns the consequences of fame through a former player, as well as through the man who expects to be his manager when True reaches the NBA.
Keywords: Basketball -- Fiction; Conduct of life -- Fiction; High schools -- Fiction; African Americans -- Fiction; School stories